The 3-H social and emotional learning cycle and the three sisters garden. (2nd January 2023) - Trundle, Kathy Cabe; Hagevik, Rita; Wheeler, Laura; Vela, Katherine N.; Parslow, Michelle; Joy, David N.
Abstract: Social connections are crucial for today's middle and high school students. We address this social need through a 3-H Social and Emotional Learning (SEL) Cycle. Through the Three Sisters Garden activity presented here, we teach secondary school students about biodiversity and sustainability as we integrate the arts into STEM (STEAM). Students investigate the growth and development of organisms from a crosscutting lens of systems. Students initiate the sensemaking process by paralleling their own need for companionship to plants. Students end the lesson by initiating a scientific argumentation for a Three (or Four) Brothers/Others Garden. The 3-H learning cycle begins and returns to social and emotional connections, giving equal weight of importance to the heart (social and emotional), hands (problem-solving), and heads (sensemaking). The lesson presented here exemplifies school garden-based learning and students' ability to initiate sensemaking of the indigenous Three Sisters Garden intercropping method. Analyzing gardens from a systems lens allows students to make emotional and cognitive connections between their own need for social connections and plants increased growth and productivity in a polyculture. When students emotionally, socially, and cognitively participate in the process of science, they begin to see themselves as a part of the scientific process.